Integrins and cadherins as therapeutic targets in fibrosis - Agarwal, Sandeep K. (Frontiers in Pharmacology, 2014)
Fibrosis is the excessive deposition of extracellular matrix proteins into tissues leading to scar formation, disruption of normal tissue architecture and organ failure. Despite the clinical large clinical impact of fibrosis, treatment options are limited. Adhesion molecules, in particular avb6 and a3b1 integrins and cadherin-11, have been demonstrated to be important mediators of tissue fibrosis. These data are reviewed here and provide the foundation for these molecules to be potential therapeutic targets for patients with fibrotic diseases.